Genetic variations in the vitamin D binding protein and season-specific levels of vitamin D among older adults - Perna, Laura; Felix, Janine F.; Breitling, Lutz Philipp; Haug, Ulrike; Raum, Elke; Burwinkel, Barbara; Schöttker, Ben; Brenner, Hermann (Epidemiology, 2013)
Background: Vitamin D insufficiency is common among older adults. Genome-wide association studies have found an association between variants in the vitamin D binding protein and serum levels of vitamin D. The quantification of this association among older women and men and its potential variation by season remain unexplored. - Methods: Serum levels of 25-hydroxyvitamin D [25(OH)D] and genetic variants in the vitamin D binding protein were analyzed in 2160 women and 1581 men age 50 to 74 years participating in a large population-based cohort study (ESTHER study—epidemiologic study assessing chances of prevention and early detection of various chronic diseases, including cancer among older adults) in Germany. Serum levels of 25(OH)D were assessed in relation to four single nucleotide polymorphisms (SNPs; rs4588, rs2282679, rs1155563, and rs12512631) by descriptive and multivariate analysis. - Results: Both heterozygous and homozygous women and men carrying the rare allele with SNPs rs4588, rs2282679, or rs1155563 had lower levels of 25(OH)D in summer months than those homozygous for the wild-type alleles. Adjusted differences ranged from 5.1 to 5.4 nmol/l among heterozygous carriers of the rare alleles and from 8.8 to 9.6 nmol/l among homozygous carriers of the rare alleles. During winter months, 25(OH)D differences by genotype were smaller among women and not apparent among men. - Conclusions: Older women and men living in a high-latitude region and carrying the rare alleles of SNPs rs4588, rs2282679, or rs1155563 seem to benefit less from higher levels of ultraviolet radiation during the summer season.